1997
DOI: 10.1164/ajrccm.156.4.9612113
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation-Perfusion Mismatch in Patients with Pleural Effusion

Abstract: Pleural effusion (PE) often causes abnormal pulmonary gas exchange. Thoracentesis is commonly used to relieve dyspnea in patients with PE, but its effect upon arterial oxygenation is varied and poorly understood. This investigation sought to: (1) characterize the distribution of ventilation-perfusion (VA/Q) ratios in patients with PE and (2) assess the effects of PE drainage by thoracentesis upon pulmonary gas exchange. We studied nine patients (two females) with a mean age of 39+/-20 (SD) yr. All of them had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 17 publications
2
81
1
3
Order By: Relevance
“…When the pleural effusion is large or chest wall compliance is reduced, effusions cause hypoxia by collapsing lung with consequent physiologic shunt [9]. Drainage of pleural effusions allowing re-expansion of collapsed lung and improvement of hypoxia, which yield variably over the subsequent 24 h and may continue for several weeks [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the pleural effusion is large or chest wall compliance is reduced, effusions cause hypoxia by collapsing lung with consequent physiologic shunt [9]. Drainage of pleural effusions allowing re-expansion of collapsed lung and improvement of hypoxia, which yield variably over the subsequent 24 h and may continue for several weeks [10].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of a total 118 patients demonstrated an overall 18% improvement in the PaO 2 /FiO 2 ratio after effusion drainage [13]. Improvement in oxygenation may occur after drainage as areas of collapsed, poorly ventilated lung reexpand, improving ventilation-perfusion matching in these areas and reducing arteriovenous shunting [9].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that lung diffusion function indicators in lung cancer group were significantly lower than those in normal control group with statistically significant difference, which mean that lung cancer may cause the decline of diffusion function. The mechanism for this may as follows: Firstly, the obstructive pneumonia, atelectasis and pleural diseases related with lung cancer can cause the reduction of lung volume, limitation of ventilation function and reduction of diffusion area, at the same time, the compensatory of surrounding lung tissue can increase the ventilation, thus cause the ventilation/perfusion imbalance [10,11]; Secondly, the blood vessels around the tumor may be blocked due to the mechanic compression, and the reduction of blood flow may increase the ventilation/perfusion ratio; Thirdly, the lung cancer cells may be transferred via the blood stream, blocking small vessels and leading to ventilation/perfusion ratio further disorder [12].…”
Section: Discussionmentioning
confidence: 99%
“…In a small number of patients, despite best efforts, it may not be possible to reach a clear diagnosis and in others it may be that treatment targeted at addressing symptoms may be a pragmatic approach preferred over and above ongoing and potentially more invasive investigations, particularly in patients with a poor prognosis. Interestingly, the removal of pleural fluid appears to result in an improvement in breathlessness not mirrored directly by the degree of improvement in gas exchange [55].…”
Section: Targeted Pleural Fluid Managementmentioning
confidence: 98%